Preparation of Refractory from local materials - Rasin, F. A.; Harby, K. H.; Moauyad, H. S.; Salam, W. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Ceramic body as a refractory was prepared by using shamoot, which is prepared by firing  kaolin Duekhla at 1450 ÂºC at 2hr ,Flint clay ,Asbestos fiber(Anthophylite type)and Sodium silicts,Phosphoric acid solution as a binder . After miling, siving ,and mixing ,samples were formed, followed that drying, firing at different temperature.     Phyical ,thermal and mechanical  properties were measured .The conclusion behind the results that the refractory prepared from; 37.5% shamoote,25% Asbestos ,37.5% Flint clay and Phosforic acid solution fired at 1300 ÂºC  gave a refractory material having  melting temperature ;1490 ÂºC, thermal shock resistance 7 cycle, thermal conductivity 2.1w/m2.K, apperant porosity 22.69% ,apperant density  2.87gm/Cm 3 ,Linear shrinkage 3.5%, compressive strength  30.43 MPa  and Impact strength 81.3J/Cm2 .